MONITORING SYSTEM OF FISH POOL WATER TURBIDITY WITH ESP32 AND BLYNK - Pribadi, Antoni; Irawan, Indra; Kumar, D. Senthil (Asia Information System Journal, 2023)
Technological developments in all aspects of life today are urgently needed, this can be seen from the many technologies that have replaced human jobs. As with the fish column at home, the work that is routinely done in the fish column is to replace the water in it if it is too cloudy so that it looks clean and creates good conditions for the development and health of the fish. Usually, fish farmers will make a schedule to check water quality and replace it. This work can sometimes take up time, especially when busyness increases and if you are late or forget to change the water in the pond, it can harm the condition of the fish in it. To help overcome this problem, equipment has been designed to monitor the turbidity level of the water that can be monitored from anywhere and at any time. This study aims to produce a tool that can monitor and control the condition of the level of water turbidity in fish ponds so that fish growth can be maximized. This monitoring is carried out regularly in real-time using IoT (Internet of Things) so that it can facilitate monitoring without the need to come directly to the pond location. This research succeeded in creating a monitoring system that can detect the turbidity of aquarium water using the ESP 32 tool and display on the Blynk application automatically in real-time.